Late Quaternary sedimentation, 50° N, North-East Newfoundland shelf - Piper, David; Mudie, Peta; Aksu, Ali; Hill, Philip (Géographie physique et Quaternaire, 1978)
Ten cores from the Northeast Newfoundland shelf and adjacent continental slope have correlable late Quaternary marine sequences. Late Holocene sediment is olive grey mud, with some ice-rafted debris. The early Holocene is characterised by warmer water microfossil assemblages, abundant ice-rafted carbonate debris, and pollen assemblages indicating open boreal woodland interspersed with tundra. Late and mid-Wisconsinan glacial stades show subarctic planktonic microfossil assemblages, regional sources of tundra pollen, storm reworking of earlier sediment, including till, and shallower water assemblages of benthonic foraminifera and diatoms. Two mid-Wisconsinan interstades are recognised, with marine microfossils similar to the early Holocene. This sequence rests disconformably on earlier (?lllinoian) pro-glacial muds which appear to overlie till.